Therapeutic revascularisation of ischaemic tissue: the opportunities and challenges for therapy using vascular stem/progenitor cells - O'Neill, Christina L (BioMed Central, 2012)
Ischaemia-related diseases such as peripheral artery disease and coronary heart disease constitute a major issue in medicine as they affect millions of individuals each year and represent a considerable economic burden to healthcare systems. If the underlying ischaemia is not sufficiently resolved it can lead to tissue damage, with subsequent cell death. Treating such diseases remains difficult and several strategies have been used to stimulate the growth of blood vessels and promote regeneration of ischaemic tissues, such as the use of recombinant proteins and gene therapy. Although these approaches remain promising, they have limitations and results from clinical trials using these methods have had limited success. Recently, there has been growing interest in the therapeutic potential of using a cell-based approach to treat vasodegenerative disorders. In vascular medicine, various stem cells and adult progenitors have been highlighted as having a vasoreparative role in ischaemic tissues. This review will examine the clinical potential of several stem and progenitor cells that may be utilised to regenerate defunct or damaged vasculature and restore blood flow to the ischaemic tissue. In particular, we focus on the therapeutic potential of endothelial progenitor cells as an exciting new option for the treatment of ischaemic diseases.